Ability to compose concept maps and student cognitive learning outcomes in animal embryology and reproduction courses - Eko Susetyarini; Endrik Nurrohman; Darioush Sharafie; Dewi Fatmawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
One of the learning outcomes of learning Animal Embryology and Reproduction is that students can explain concepts about reproduction or embryology theory. Since concept map-based learning can improve students’ critical thinking skills and analysis, and support their interest in learning, this study analysed the ability of students enrolled in the 2019/2020 Animal Embryology and Reproduction course to construct concept maps and students' cognitive learning outcomes through assignments and tests. This descriptive study involved 127 students in semester VI enrolled in the Embryology and Animal Reproduction programme at the Department of Biology Education, FTTE at the Universitas Muhammadiyah Malang. The sampling technique was saturated sampling and the data were collected through the task of compiling concept maps and learning outcomes with tests. The drafting of concept maps was assessed by the concepts and ideas, relationships between concepts, hierarchies, propositions, and spelling, with cognitive learning assessed by tests. The results showed that most students had sufficient ability to compose a concept map and very good learning outcomes, indicating that concept maps can be used to learn biology in Animal Embryology and Reproduction courses.